User satisfaction of E-homestay portals in Malaysia - Rizal Hamid; Hanudin Amin; Soffri Yussof; Ku Chen-Jung; Suddin Lada; Syed Nasirin (2018)
The Internet has significantly improved the quality of consumers’ decision when making online bookings for homestays which is an emerging segment of hospitality in Malaysia. Drawing from DeLone and McLean’s Theory of Information System Success, this study examines the effects of information quality, system quality, and electronic service quality on user’s satisfaction of e-homestay portals. Data were collected from homestay lodgers (N=187) in Malaysia. The study reports that the antecedents of information quality, system quality and electronic service quality positively correlates with user’s satisfaction. These results provide better understanding for the service providers to better plan their homestay portals to meet the expectation of potential users. The present study also highlights the significance of homestays lodging for the hospitality and tourism industry in Malaysia. Limitations of the study and future works are noted and discussed.